Mutant IDH1 cooperates with NPM1c or FLT3 ITD to drive distinct myeloid diseases and molecular outcomes - Takashi Sakamoto; Julie Leca; Xin Zhang; Cem Meydan; Jonathan Foox; Parameswaran Ramachandran; Liam D. Hendrikse; Wenjing Zhou; Thorsten Berger; Jerome Fortin; Steven M. Chan; Ming-Feng Chiang; et al. (Proceedings of the National Academy of Sciences, 2025)
In human acute myeloid leukemia (AML), mutations of isocitrate dehydrogenase-1 ( IDH1 ) often co-occur with NPM1 mutations, and less frequently with FLT3 mutations. To investigate whether the effects of IDH1 mutation differ according to the specific co-occurring mutation, we generated two strains of double knock-in mutant mice. Idh1 R132H combined with Npm1c induced overt AML, whereas Idh1 R132H plus Flt3 ITD resulted in Flt3 ITD -driven myelo- or lymphoproliferation that was minimally affected by Idh1 R132H and rarely generated AML. Gene expression profiling revealed differences between Idh1 R132H ; Npm1c cells and Idh1 R132H ; Flt3 ITD cells and suggested altered heme metabolism and immune responses in the former. The profile of Idh1 R132H ; Npm1c cells corresponded to that of human IDH -mutated AML cells, particularly those resistant to inhibitors of mutant IDH. Compared to treatment with a menin inhibitor, IDH1-targeted therapy of Idh1 R132H ; Npm1c AML-bearing mice was less efficacious in improving cell differentiation and extending survival. The differential cooperation of Idh1 R132H with Npm1c vs. Flt3 ITD may have implications for the devising of subtype-specific treatments for human AML.